Sekolah Inklusi Sebagai Pengembangan Karakteristik SMP Muhammadiyah 1 Godean - Ithma Panggalih; Didi Kardo; Natasa Olandari (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
In the world of education, especially for teaching staff, knowing each student's characteristics is very important, this really helps teaching staff in adjusting teaching and learning methods. Especially for students who have physical limitations or whose IQ is below average. In every learning process, not everything is carried out smoothly, there are some students who experience learning difficulties and ultimately cannot achieve the appropriate learning targets. Inclusive education is one of the educational institutions presented by the government with the aim of providing opportunities for students with special needs or students who have special talents and intelligence to get education like regular students without looking at differences. Placement of students with special needs needs to pay attention to the potential, type and level of impairment or need.